Persoalan asas ISO 14000 - Ismail, Hamidi; Syed Hussain, Tuan Pah Rokiah (Penerbit Universiti Utara Malaysia, 2006)
This book explains the implementation, importance and role of the ISO 14000 Standard. It also discusses on how the legislation process of the ISO document is formed. This book is suitable to university students as well as general leaders who yearn to obtain a deep comprehension on the standard of nature management.